EFFFECTS OF INTENSITY AND DURATION OF EXERCISE ON DIFFERENTIAL LEUCOCYTE COUNT - Ali, Shaukat; Ullah, Farman; Jan, Rahat (Journal of Ayub Medical College Abbottabad, 2003)
Background: Increases in neutrophils, lymphocytes and monocytes account for the exercise induced leucocytosis, related to work loads and duration of exercise. To observe the effects of intensity and duration of exercise on differential leucocytes count, two groups of normal healthy male adult subjects were exercised on treadmill for different duration and intensities. Methods: Group-I subjects (n=15) performed exercise by running for a duration of 2-3 minutes, at 7% grade (4 degree inclination) and at speed ranging from 7.5 to 9 Km/hour, while group-II subjects (n=15) walked on treadmill for a duration of 7-10 minutes at zero grade and at Speed ranging from 5 to 6 Km/hour. Pricking the tip of finger with a lancet under sterilized conditions at three occasions i.e. before exercise, immediately after and 30 minutes after exercise, a drop of blood was taken. Each drop of blood was put on a neat and clean glass slide to make film for differential leucocytes count. The samples were then analyzed by standard methods and evaluated artistically. Results: In group-I subjects, neutrophils were significantly increased by 5.97% immediately after exercise and were significantly decreased by 13.471% after 30 minutes rest and so the neutrophils were 8.454% below baseline (p<.0.001) 30 minutes after exercise. Lymphocytes were significantly increased by 19.57%, 30 minutes after exercise and were 17.734% above baseline (p<0.001) Eosinophils were significantly increased by 38.042% after 30 minutes rest and were 33.333% below baseline (p<0.01). Basophiles were 50.187% less (p<.0.01) 30 minutes after exercise than pre-exercise. In-group II, neutrophils were significantly increased by 4.30%, immediately after exercise and then decreased significantly by 6.019%, after 30 minutes rest. On the other hand, lymphocytes were significantly decreased by 11.981%, immediately after exercise and then increased significantly by 12.379%, after 30 minutes rest. Conclusions: It clearly indicates that the exercise of high intensity and less duration has greater effect on neutrophil count. The increase in lymphocyte count, 30 minutes after exercise, clearly indicate that exercise of low intensity and longer duration is helpful in improving acquired immunity. Key Words: Exercise Intensity, Duration, DLC